The only disability in life is a bad attitude: teachers' perceptions on the need for promoting positive attitudes among non-disabled students towards disabled people and the strategies thereof - Kaltsaka, Christina (2015)
3 Abstract Despite worthy legislation, disabled people still face exclusionary practices and barriers to social inclusion. Since attitudinal barriers are one of the major obstacles standing in the way of positive change, recent literature focuses on the imperative need to promote positive attitudes of non-disabled children towards disabled people in order to raise citizens with an inclusive mindset and establish inclusive societies. This dissertation seeks to explore Greek schools’ response to the issue in terms of teaching practices. The insights offered from the analysis of the data contribute to indications about schools’ current approach in challenging negative attitudes and offer implications for educational and professional development in the Greek setting. The investigation takes the form of a small-scale qualitative research. Data are gathered through semi-structured interviews with seven Greek primary school teachers, employed in mainstream schools in Athens, and later analysed using the qualitative content analysis method. Findings illustrate that teachers acknowledge the need for promoting positive attitudes towards disabled people and the importance of relevant teaching; however, their practical engagement is limited due to insufficient resources and support. Keywords: disability, attitudes, anti-disablist education, Greek primary school teachers